2016
DOI: 10.3759/tropics.24.169
|View full text |Cite
|
Sign up to set email alerts
|

The effect of forestland allocation to the livelihoods of local people in the North Central Coast of Vietnam: A case in Nam Dong district

Abstract: Forestland allocation (FLA) policy in Vietnam aimed at conserving forests and improving local livelihoods.In regard to the effectiveness of FLA, some authors reported improvements in forest cover and quality, whereas others stated inappropriate implementation process and minor impacts on household income. Hence, this study examined whether disturbances in initial stage still existed, how allocated forestlands were utilized, and how FLA contributed to local livelihoods under different forest management regimes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…While the local scale of this study limits the ability to make exhaustive policy recommendations, our findings may still provide insightful lessons on how national policies may be improved within and beyond commune borders. Indeed, similar policy outcomes had been found in other Vietnamese highland communes, such as feedbacks between forest degradation, flood-related damages, and food insecurity [23]; an impact of landscape heterogeneity on land use decisions [20,25]; or a coupling of livelihood to wood and agricultural markets [10,20,25].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…While the local scale of this study limits the ability to make exhaustive policy recommendations, our findings may still provide insightful lessons on how national policies may be improved within and beyond commune borders. Indeed, similar policy outcomes had been found in other Vietnamese highland communes, such as feedbacks between forest degradation, flood-related damages, and food insecurity [23]; an impact of landscape heterogeneity on land use decisions [20,25]; or a coupling of livelihood to wood and agricultural markets [10,20,25].…”
Section: Discussionmentioning
confidence: 60%
“…Some case studies reported overall positive effects on forest resources and livelihoods [20,21]. Other case studies, however, reported continued degradation and deforestation of natural forests following the implementation of FLA policies, while only commercial tree plantations increased in area [10,[22][23][24]. Furthermore, improvements in the local livelihood were reported to be either small [23] or disproportionally larger for some population groups compared to others, such as for Kinh people, the ethnic majority in Vietnam, compared to ethnic minority members [10,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also indications of gender impacts, as women's interests in tree planting often focus on multifunctional agroforestry, food security, and fuelwood production (which have tended to be de-emphasized in reforestation projects), while men have sought out income increasing opportunities (Nguyen et al 2016b, Villamor et al 2017). Women have often provided labor for tree planting within households, but rarely have controlled decision-making about the forest plot (Richards 2019).…”
Section: Benefits Distributionmentioning
confidence: 99%
“…During the 1990s many communities were re-settled by government programs from remote areas to the main A Lưới Valley, with the emptied areas subsequently being developed for hydro-electric dams, for nature conservation, and for timber production forestlands of state-owned forest companies (SFCs) [27,[31][32][33][34]. Swidden agriculture and many forest uses were prohibited by law, impelling the communities to adopt new, more intensive forms of agricultural land management and monocrops (rice, cassava, acacia plantations, aquaculture), at the sacrifice of diverse traditional methods of resource production and subsistence [1,26,27,[35][36][37][38][39]. Conversely, in some communes (e.g., Ðông Sơn) where soils were contaminated with dioxins from the spraying and spilling of the defoliant Agent Orange during the war [40], the planting of acacias may also have provided new lower-risk agricultural opportunities.…”
Section: The Study Area Within Geographic-historic Contextmentioning
confidence: 99%